Epidemiology of Neuromyelitis Optica in the World: A Systematic Review and Meta-Analysis - Taherioun, Maryam; Khalili, Behrang; Nasr, Zahra; Etemadifar, Masoud; Vosoughi, Reza (Multiple Sclerosis International, 2015)
Background. Neuromyelitis optica (Devic’s disease) is a severe autoimmune inflammatory disorder of the central nervous system. Epidemiological aspects of NMO have not been systemically reviewed. In this study we systematically reviewed and assessed the quality of studies reporting the incidence and/or prevalence of NMO across the world. Methods. A comprehensive literature search using MEDLINE, EMBASE, and Web of Science for the terms “Neuromyelitis optica,” “devic disease,” “incidence,” “prevalence,” and “epidemiology” was conducted on January 31, 2015. Study quality was assessed using an assessment tool based on recognized guidelines and designed specifically for this study. Results. A total of 216 studies were initially identified, with only 9 meeting the inclusion criteria. High level of heterogeneity amongst studies precluded a firm conclusion. Incidence data were found in four studies and ranged from 0.053 per 100,000 per year in Cuba to 0.4 in Southern Denmark. Prevalence was reported in all studies and ranged from 0.51 per 100,000 in Cuba to 4.4 in Southern Denmark. Conclusion. This review reveals the gaps that still exist in the epidemiological knowledge of NMO in the world. Published studies have different qualities and methodology precluding a robust conclusion. Future researches focusing on epidemiological features of NMO in different nations and different ethnic groups are needed.